Waqf Fintech Innovation: Opportunities, Challenges, and Increasing Community Waqf Literacy - Ramadhan, Taufiq; Taufik; Bayu Arif Mahendra; Nur Majdina (Veteran Law Review, 2025)
This study aims to identify the role of fintech innovation in improving public literacy on endowments (wakaf) in Indonesia, as well as the opportunities and challenges in its implementation. Although the potential of endowments in Indonesia is vast, public understanding of its concepts and benefits remains limited. The research gap shows that the traditional and opaque management of endowments requires innovation to optimize it. Fintech innovation can bridge this gap by offering digital platforms that ease access and enhance transparency in endowment management. The research method used is a qualitative approach with a literature review, collecting data from relevant written sources, such as books, articles, and journals. Data analysis follows the Miles and Huberman interactive model, involving data reduction, presentation, and conclusion drawing. The results show that fintech for endowments has significant potential to improve public literacy through digital platforms that provide comprehensive and easily accessible information. However, this innovation also faces challenges such as unclear regulations, low digital literacy, and security threats. Therefore, collaboration among the government, endowment institutions, and fintech providers is necessary to develop clear regulations, improve digital literacy, and ensure transaction security. With these steps, fintech for endowments can effectively optimize the potential of endowments as an Islamic philanthropy instrument.